Effect of Formaldehyde on Rat Testis Structure - Abdelmonem Awad Hegazy; Nadia ElAbassery Elsayed; Marwa Mahmoud Ahmad; Nehal Mohammad Omar (Academia Anatomica International, 2017)
Background: Formaldehyde is found in different kinds of medicine and industrial products, cigarette smoke, and even numerous vegetables, fruits and seafood that have been illegally preserved with formalin. The aim of this study was to investigate the effects of formaldehyde on adult albino rat testes through light microscopic examination, immunohistochemistry, biochemistry, morphometry and statistical analysis. Methods: Thirty adult male albino rats were utilized in this work. These animals were equally divided into three main groups, with 10 animals each. Group I (control group): The animals were injected with intraperitoneal sterile physiological saline. Group II animals were injected intraperitoneally with a daily dose of formaldehyde (5 mg/kg body weight "BW") for 30 days. Group III animals were injected intraperitoneally with a daily dose of formaldehyde (10 mg/kg BW) for 30 days. By the end of the experiment, blood samples were collected for biochemical study of testosterone; and all animals were anaesthetized and testis specimens were dissected out and weighted then subjected to histological, immunohistochemistry, and morphometric examination. Results: Administration of formaldehyde at a dose of 5 and 10 mg/kg caused a decrease in serum testosterone. Moreover, it caused a decrease in the testis weights and induced several histopathological changes in the testis of adult male albino rats such as atrophy of seminiferous tubules with absence of sperm bundles and degeneration of germ. It also increased the collagen fibers deposition in testis as evidenced by Masson`s trichrome staining. The testis showed a positive immune reaction to 8-hydroxy-2'-deoxyguanosine. Conclusion: Exposure to formaldehyde is suggested to result in some testicular damage. It is suggested that special precautions might be taken to limit the occupational and environmental formaldehyde exposure; and to prevent or even minimize its contamination with food and water.